Molecular autopsy and family screening in a young case of sudden cardiac death reveals an unusually severe case of FHL1 related hypertrophic cardiomyopathy. Issue 8 (10th July 2019) - Gaertner‐Rommel, Anna; Tiesmeier, Jens; Jakob, Thomas; Strickmann, Bernd; Veit, Gunter; Bachmann‐Mennenga, Bernd; Paluszkiewicz, Lech; Klingel, Karin; Schulz, Uwe; Laser, Kai T.; Karger, Bernd; Pfeiffer, Heidi; et al.
Abstract: Background: Hypertrophic cardiomyopathy (HCM) is a genetic cardiomyopathy with a prevalence of about 1:200. It is characterized by left ventricular hypertrophy, diastolic dysfunction and interstitial fibrosis; HCM might lead to sudden cardiac death (SCD) especially in the young. Due to low autopsy frequencies of sudden unexplained deaths (SUD) the true prevalence of SCD and especially of HCM among SUD remains unclear. Even in cases of proven SCD genetic testing is not a routine procedure precluding appropriate risk stratification and counseling of relatives. Methods: Here we report a case of SCD in a 19‐year‐old investigated by combined forensic and molecular autopsy. Results: During autopsy of the index‐patient HCM was detected. As no other possible cause of death could be uncovered by forensic autopsy the event was classified as SCD. Molecular autopsy identified two (probably) pathogenic genetic variants in FHL1 and MYBPC3 . The MYBPC3 variant had an incomplete penetrance. The FHL1 variant was a de novo mutation. We detected reduced FHL1 mRNA levels and no FHL1 protein in muscle samples suggesting nonsense‐mediated mRNA decay and/or degradation of the truncated protein in the SCD victim revealing a plausible disease mechanism. Conclusion: The identification of the genetic cause of the SCD contributed to the rational counseling of the relatives and risk assessment within the family. Furthermore our study revealed evidences for the pathomechanism of FHL1 mutations. Abstract : We report an unusual case of hypertrophic cardiomyopathy identified by combined advanced post resuscitation care and molecular autopsy in a young sudden cardiac death victim. The present study shows the relevance of implementing emergency medicine, forensic and molecular autopsy to unravel the cause of SCD cases.